Pengaruh Motivasi Dan Kepemimpinan Terhadap Kinerja Karyawan Operational Dengan Employee Engagement Sebagai Variabel Intervening Pada Pt Global Bintang Timur Ekspress ( Gbte) - Rusianto, Michael; Rachmawati, Ike; Fathorrahman (PROGRAM PASCA SARJANA MAGISTER MANAJEMEN INSTITUT TEKNOLOGI DAN BISNIS ASIA MALANG, 2025)
PT Global Bintang Timur Ekspress is an expedition company, one of the J&T group, although this company was established in 2015 in Indonesia, this company is a Chinese company. The top positions from manager to director are mostly native republic of china / Indonesians who can speak mandarin. This makes some problems that occur operationally not well communicated between operational leaders and management leaders. It is not uncommon for communication limitations to be one of the things that cause internal conflicts such as high turnover in operations. However, not a few operational employees have survived from 2015 to the present. Based on this phenomenon, a study was conducted that aims to determine and analyze 1) The effect of motivation on employee engagement, 2) The effect of motivation on employee performance, 3) The effect of leadership on employee engagement, 4) The effect of leadership on employee performance, 5) The effect of employee engagement on employee performance, 6) The effect of motivation on employee performance through employee engagement as an intervening variable, 7) The effect of leadership on employee performance